The Influence of Axle Load Distribution of Machine-Tractor Aggregates on the Dip of the Wheel-Track - Shyla, I. N.; Ramaniuk, N. N.; Orda, A. N.; Nukeshev, S. O. (Selʹskohozâjstvennye mašiny i tehnologii (Online), 2018)
It is defined that while doing some agricultural operations the area covered by the machine-tractor aggregates wheels exceeds the area of the field. (Purpose of research) The regularity of repeated accumulation of the soil puddling and the influence of the specifity of axle load distribution of machine-tractor aggregates on the dip of the wheel-track is justified. (Materials and methods) The mathematical apparatus to describe the influence of the effects connected with the soil particles reposition while the repeated loading is developed. The over consolidated soil creates some raised resistance while the following tillage which results in increased fuel consumption and lost productivity of machine-tractor aggregates. The modified soilstructure is difficult to be restored entirely. As a result the intensive worked tilth top soil degrades with time which creates the ecosystem disbalance of cultivated land. The laboratory experiments of the soil features influence and the specifity of wheel loading on the dip of the wheel-track are performed. The regularity of repeated puddling accumulation being subject to Bolstman correlation which links the process entropy and the probability of this state (statistical interpretation of the principle of entropy increase) is set. (Results and discussion) The dependences to determine the deformation of soil with various physical and mechanical properties under different drive system loading conditions of machine-tractor aggregates are obtained. The influence of axle load distribution on the dip of the wheel-track is established. The dependence to describe the process of wheel track formation on the sod-podzolic sandy loam soil of low moisture level which corresponds to the empirical data is obtained. The calculations from the dependence obtained are performed. While doing repeated passes the wheel sinkage is provided only by the increase of contact stresses. (Conclusions) The regularity of the soil puddling rise from the deformer while the repeated loading is set. The regularity obtained makes possible to define the soil deformation depending on the different operating conditions and the drive system parameters of machine-tractor aggregates on different types of soil.